Lifespan Extension and Sustained Expression of Stem Cell Phenotype of Human Breast Epithelial Stem Cells in a Medium with Antioxidants - Kai-Hung Wang; An-Pei Kao; Chia-Cheng Chang; Ta-Chin Lin; Tsung-Cheng Kuo (Hindawi Limited, 2016)
We have previously reported the isolation and culture of a human breast epithelial cell type with stem cell characteristics (Type I HBEC) from reduction mammoplasty using the MSU-1 medium. Subsequently, we have developed several different normal human adult stem cell types from different tissues using the K-NAC medium. In this study, we determined whether this low calcium K-NAC medium with antioxidants (N-acetyl-L-cysteine and L-ascorbic acid-2-phosphate) is a better medium to grow human breast epithelial cells. The results clearly show that the K-NAC medium is a superior medium for prolonged growth (cumulative population doubling levels ranged from 30 to 40) of normal breast epithelial cells that expressed stem cell phenotypes. The characteristics of these mammary stem cells include deficiency in gap junctional intercellular communication, expression of Oct-4, and the ability to differentiate into basal epithelial cells and to form organoid showing mammary ductal and terminal end bud-like structures. Thus, this new method of growing Type I HBECs will be very useful in future studies of mammary development, breast carcinogenesis, chemoprevention, and cancer therapy.